New records of stink bugs (Hemiptera: Pentatomidae) from Colombia - Castro-Huertas, Valentina; Schwertner, Cristiano F.; Fernández, Fernando (Zootaxa, 2015)
New records of genera and species of stink bugs (Hemiptera: Pentatomidae) from Colombia are provided. Two genera are new records for South America: Alathetus and Schraderiellus. Fifteen genera are new record for Colombia: Agaclitus, Boea, Ceratozygum, Euthyrhynchus, Eritrachys, Doesburguedessa, Lopadusa, Marmessulus, Paralincus, Patanius, Peromatus, Phalaecus, Phoeacia, Rio, and Tyrannocoris. Forty-nine species from five subfamiles are recorded for the first time in Colombia. Asopinae: Coryzorhaphis carneolus Erichson, Coryzorhaphis superba Breddin, Euthyrhynchus floridanus (Linnaeus), Podisus sagitta Fabricius, Stiretrus anchorago (Fabricius), Stiretrus cinctellus Germar, Tylospilus peruvianus Horvath, Tyrannocoris nigriceps Thomas. Cyrtocorinae: Ceratozygum horridum (Germar). Discocephalinae: Agaclitus dromedarius Stål, Antiteuchus melanoleucus (Westwood), Antiteuchus sepulcralis (Fabricius), Dinocoris gibbosus (Fallou), Dinocoris variolosus (Linnaeus), Discocephalessa terminalis (Walker), Dryptocephala crenata Ruckes, Dryptocephala dentifrons (Latreille), Eurystethus ovalis Ruckes, Paralcippus dimidiatus (Ruckes), Alathetus rufitarsus Dallas, Eritrachys bituberculata Ruckes, Paralincus bimaculatus (Ruckes), Schraderiellus cinctus (Ruckes), Xynocoris recavus (Garbelotto & Campos). Edessinae: Brachystethus cribus (Fabricius), Brachystethus tricolor Bolívar, Doesburguedessa elongatispina Fernandes and Lopadusa fuscopunctata (Distant). Pentatominae: Banasa fulgida Thomas, Banasa paraexpallescens Thomas, Dichelops divisus (Walker), Dichelops nigrum Bergroth, Euschistus carbonerus Rolston, Mormidea bovilla (Distant), Mormidea triangularis (Walker), Murgantia bifasciata Herrich-Schaeffer, Murgantia violascens (Westwood), Oebalus pugnax (Fabricius), Oebalus ypsilon-griseus (DeGeer), Odmalea concolor (Walker), Patanius vittatus Rolston, Proxys albopunctulatus (Palisot), Proxys punctulatus (Palisot), Rhyncholepta grandicallosa Bergroth, Rio insularis Ruckes, Roferta marginalis (Herrich-Schäffer), Serdia concolor Ruckes, Sibaria armata (Dallas) and Taurocerus achilles (Stål). These new records for Colombia are importanst for the understanding of the distributional range of the genera and species involved.